Labor Dance sebagai Pendekatan Alternatif Non-Farmakologis untuk Mengurangi Nyeri Persalinan: Literatur Review - Pratiwi, Dian; Lestari, Pratiwi Puji (POLTEKKES KEMENKES MANADO, 2025)
Background: Labor pain is a major physiological and psychological challenge faced by women during childbirth. The use of non-pharmacological methods such as labor dance is increasingly being considered because of its effectiveness in reducing pain without causing pharmacological side effects. Objective: This study aims to analyze the effectiveness of labor dance interventions in reducing labor pain, increasing labor satisfaction, and its effects on neonatal outcomes. Method: This study is a literature review of seven articles covering various RCT designs, involving pregnant women in the active phase of labor. Data were reviewed based on pain intensity (VAS), anxiety levels, maternal satisfaction, perception of labor trauma, and neonatal outcomes. Results: The majority of study results showed that labor dance was effective in significantly reducing labor pain scores at 30 and 60 minutes after the intervention. In addition, this method contributed to increased maternal satisfaction, decreased perception of labor trauma, and better neonatal outcomes, including Apgar scores and infant oxygen levels. Several studies reported that the effects on anxiety and labor duration were not always statistically significant. Conclusion: Labor dance is an effective, inexpensive, and safe non-pharmacological approach to reducing pain and improving the labor experience. This method can be integrated into routine midwifery practice by involving the couple as active supporters.